DWA TECHNIQUE TO IMPROVE DAC OF SIGMA-DELTA FRACTIONAL-N FREQUENCY SYNTHESIZER FOR WIMAX - Ziboon, H T; Azzawi, H M (Al-Nahrain Journal of Science, 2018)
A first order of DWA (Data Weighted Averaging) algorithm with third order sigma-delta modulator is proposed for application in sigma-delta fractional-N frequency synthesizer for WiMAX. In addition, this paper discusses the impact of mismatch between Digital-to-Analog convertor (DAC) unit elements. The simulation results show the effectiveness of the DWA technique in reduction of spurs, also DWA technique proves its ability to solve DAC unit elements mismatch. The fractional spur noise is converted into a broadband. Quantization noise with DWA is improved by – 10 dB if the element mismatch 0.01 and – 5 dB if the element mismatch 0.08 with 8 bit PFD/DAC. Matlab (V.7) program is used for simulation.